2019
DOI: 10.1155/2019/3101987
|View full text |Cite
|
Sign up to set email alerts
|

The Antiobesity Effects of Buginawa in 3T3-L1 Preadipocytes and in a Mouse Model of High-Fat Diet-Induced Obesity

Abstract: There has been a remarkable interest in finding lipid inhibitors from natural products to replace synthetic compounds, and a variety of oriental medicinal herbs are reported to have biological activity with regard to lipid inhibition. Buginawa (Bugi) is a novel combined formula that contains twelve medicinal herbs with potential for weight loss induction. We hypothesized that Bugi may have antiobesity effects in 3T3-L1 preadipocytes and in a high-fat diet- (HFD-) induced mouse model. In this study, 3T3-L1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 61 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…4 Serum CEBPα, FAS, PPARγ, and SREBP1 levels in rats exposed to NP (n = 10). a vs C group, P < 0.05, b vs L group, P < 0.05, c vs M group, P < 0.05 In the current research on the association between NP and obesity, exposure to NP during perinatal period increased body weight, fat weight, serum total cholesterol and glucose levels [24]; NP could be a potential chemical stressor for obesity and obesity-related diseases. However, in some experiments, the exposure duration of NP was short, mostly acute and subacute, and the NP dose was high.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…4 Serum CEBPα, FAS, PPARγ, and SREBP1 levels in rats exposed to NP (n = 10). a vs C group, P < 0.05, b vs L group, P < 0.05, c vs M group, P < 0.05 In the current research on the association between NP and obesity, exposure to NP during perinatal period increased body weight, fat weight, serum total cholesterol and glucose levels [24]; NP could be a potential chemical stressor for obesity and obesity-related diseases. However, in some experiments, the exposure duration of NP was short, mostly acute and subacute, and the NP dose was high.…”
Section: Discussionmentioning
confidence: 77%
“…The exposure dose increased, the red color became deeper, and the fat cells were more densely distributed; WB results showed the protein expressions of CEBPα, FAS, SREBP1, and PPARγ increased in adipocytes. 3T3-L1 pre-adipocyte in vitro experiments are often used to evaluate the interference of environmental chemicals on adipogenesis, and provide a basis for environmental substances that can affect lipid metabolism in the body [5,10,24]. Studies have shown that [11,17]: 4-NP increased PPARγ activity at 1 μM, and significantly promoted triglyceride accumulation in 3T3-L1 adipocytes at 10 μM.…”
Section: Discussionmentioning
confidence: 99%
“…3T3-L1 preadipocytes were obtained from the American Type Culture Collection (ATCC, Manassas, VA, USA; CL-173) and were cultured in DMEM containing 10% BS, 1% ABAM, 1 g/l HEPES, and 1.5 g/l sodium bicarbonate. The 3T3-L1 adipocyte differentiation was performed as previously described [22]. To stimulate adipocyte differentiation, cells were seeded at a density of 2 × 10 5 per well into 6-well plates to confluence (day 0).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was performed was previously described [22]. 3 T3-L1 preadipocytes (1 × 10 4 cells per well) were seeded on 96-well plates at density 1 × 10 4 cells per well.…”
Section: Cell Viability Assaymentioning
confidence: 99%
See 1 more Smart Citation